2003
DOI: 10.1042/bj20021266
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of targets of mTOR (mammalian target of rapamycin) signalling by intracellular amino acid availability

Abstract: In mammalian cells, amino acids affect the phosphorylation state and function of several proteins involved in mRNA translation that are regulated via the rapamycin-sensitive mTOR (mammalian target of rapamycin) pathway. These include ribosomal protein S6 kinase, S6K1, and eukaryotic initiation factor 4E-binding protein, 4E-BP1. Amino acids, especially branched-chain amino acids, such as leucine, promote phosphorylation of 4E-BP1 and S6K1, and permit insulin to further increase their phosphorylation. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
180
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(194 citation statements)
references
References 62 publications
10
180
4
Order By: Relevance
“…Although a separate signaling pathway starting at the plasma membrane cannot be excluded, the available evidence indicates that mTOR-dependent signaling is stimulated by intracellular amino acids, rather than extracellular amino acids (leucine in particular). 41 In another study, carried out with C2C12 myotubes, 42 similar observations were made. Rapamycin was found to stimulate autophagic proteolysis, but could not abolish the Figure 1 Diagram of autophagy signaling.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 53%
See 1 more Smart Citation
“…Although a separate signaling pathway starting at the plasma membrane cannot be excluded, the available evidence indicates that mTOR-dependent signaling is stimulated by intracellular amino acids, rather than extracellular amino acids (leucine in particular). 41 In another study, carried out with C2C12 myotubes, 42 similar observations were made. Rapamycin was found to stimulate autophagic proteolysis, but could not abolish the Figure 1 Diagram of autophagy signaling.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 53%
“…As indicated above, in a variety of cell types, including hepatocytes, mTOR has an absolute requirement for amino acids, and is not activated by insulin alone. Sufficient amounts of amino acids from endogenous origin must apparently have been present in these studies (also see Beugnet et al 41 ). According to the authors, 40 amino acids use an mTOR-independent pathway which is initiated by binding one or more amino acids, presumably leucine, to an aminoacid receptor protein in the plasma membrane, which then somehow leads to an inhibition of autophagy that is independent of mTOR.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 98%
“…Furthermore, only a fraction of maximal mTORC1 activity (~30%) is required to fully saturate muscle protein synthesis [98,99]. The amino acid sensing by mTORC1 also seems to be driven not by extracellular, but instead by intracellular amino acid concentrations [100]. The mechanisms by which this occurs are incredibly complex and not yet fully defined.…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%
“…The mTOR (mammalian target of rapamycin) has been identified as a negative regulator of autophagy in mammalian cells [38,39]. Many studies have demonstrated that rapamycin is a potent stimulator of autophagy by inhibiting mTOR [39,40], and rapamycin treatment has been shown to provide protection against I/R injury in Langendorff perfused rat hearts [41]. However, mTOR regulates multiple metabolic pathways in addition ot autophagy.…”
Section: Autophagy In Ischemia and Reperfusionmentioning
confidence: 99%